The effect of linguistic propositions on the collection of Arabic language norms and the development of critical thinking among middle-grade students. - Raed Rsim Younis Zaydi (Zanco Journal of Humanity Sciences)
The reality of teaching the Arabic language rules is not satisfactory, as the pedagogical methods used do not help students develop their mental skills, especially critical thinking skills. They are often traditional in terms of teaching students, who are passive, passive, often passive, active, and often active, their listening task, and the teacher's task of narrating facts and judgments. It is a blind simulation student, a dependency on others, and a weak spirit of creativity, innovation, and opinion. The opinions of educators and teachers almost agree on the reasons for students' weakness in learning the rules of Arabic, and that the reason lies in the way of teaching. The difficulty or the ease of the rules of Arabic does not lie in the same rules, but in the teaching method The study was aimed at learning the impact of language pros on Arabic language proficiency and development of critical thinking among middle-grade students. In order to achieve the two search goals, the two sub-researchers have developed the following two hypothmia: —there is no statistically significant difference at an indication level (0.05) between the average scores of experimental group students who study using language. Among the average scores of control group students who study the traditional method of the dimensional test. —there is no statistically significant difference at an indication level (0.05) between the average grade of the group's experimental students in the pre- and dimensional quiz in the critical thinking scale. The search sample (63) students reached. The final sum of the sample to which the test will be applied (30) became students for each of the two research groups, and rewarded the researcher between the two groups in a set of variables. The researcher has relied on two tools (the test of inquiry) and (the critical thinking test) and has extracted their cycometric properties. The researcher used statistical methods (T/K Box/Pearson Link) . The search resulted in the following results: – a statistically significant difference for the experimental group in the dimensional test. – there is a statistically significant difference in favor of a dimensional application of critical thinking testing. In the light of the findings of the researcher, it is possible to conclude the following: 1. The use of language (language) contributes to the raising of the level of first grade students in Arabic grammar, as the results of the research show that the experimental group is superior to the control group. Within the results of this research, which has shown a positive impact on the group's trial, the following recommendations can be made: 1. The adoption of an effective method of teaching Arabic grammar to middle grade students. Following this research, the researcher suggests the following: 1. Conduct a similar study of current study in variables other than achievement such as: (Development of trends and trends, development of innovative thinking, critical thinking, and trend toward science).